Partnering with periodontal patients and care providers to establish research priorities for patient engagement in specialized periodontal care: A study protocol - Arnaldo Perez; Manuel Lagravere; Cristine Miron Stefani; Ava Nasr Esfahani; Geoff Ball; Monica Gibson (PLoS ONE, 2025)
Introduction Periodontitis is highly prevalent and disproportionately affects vulnerable populations, including older adults, racial and ethnic minorities, and low-income individuals. While periodontal therapies are largely effective, patient engagement in periodontal care is problematic. The study describes in this protocol aims to identify the top ten research priorities or uncertainties for specialized periodontal care (SPC) that are most important to periodontal patients and care providers. Methods The James Lind Alliance approach will guide the priority-setting partnership (PSP), which involves several steps: forming a PSP steering committee, gathering potential research uncertainties, summarizing the research uncertainties, verifying unanswered uncertainties, completing an interim priority setting survey, and facilitating a priority setting workshop. Study participants will be periodontal patients (n ~ 150) and care providers (n ~ 120), including general dentists, periodontists, and dental hygienists in Alberta, Canada. A steering committee representing the four stakeholder groups will oversee the study. Data on uncertainties from these groups will be gathered through two online surveys and focus groups. Demographic data (e.g., age, sex) will be collected to describe participants and ensure representation of all stakeholder groups. Uncertainties submitted by participants will be evaluated against the existing evidence gathered through a scoping review to determine if they have already been addressed. Unanswered uncertainties will be taken to a workshop where participants (n ~ 20) representing all the stakeholder groups will set the top ten research priorities. Data analysis will include descriptive statistics and content analysis. The study is expected to conclude in August 2026. Conclusion Study findings will be disseminated to raise awareness among researchers and funders on research priorities that matter most to patients and dental care providers regarding patient engagement in SPC.